Moisture Content Distribution in Capillary and Porous Body at Initial and First Drying Periods - S. N. Osipov; V. A. Bilyk (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper provides analytical solution of the Pick second law that makes it possible to calculate moisture distribution in cross-section of ceramic plate at initial and first drying periods taking into account exponential increase in its time intensity. The paper shows necessity to take into account an increase in diffusion coefficient value in the case when temperature of ceramic mass becomes higher.